Exploring SEO Techniques for Web 2.0 Websites - Nazar, Najam (My University, 2009)
Search Engine Optimization is an Internet marketing strategy and a process, widely used nowadays for improving the volume or quality of traffic to a website through search engines. The results generated by search engines can be natural (organic or algorithmic) and/or paid search. In this thesis report, I have discussed different techniques used for achieving better optimization for Web 2.0 based websites. Different techniques related to SEO like keyword discovery, crawling, on-page and off-page optimization and different Google tools are discussed. This study also describes the impact of SEO on Internet marketing. The results from my discussion and investigation will help webmasters to gain a deep insight about SEO and also to guide them in making better decisions regarding their online advertising and marketing campaign.
Keywords: Information Technology; Informationsteknik